Case study of air transport in Barbados: a decade of evolution - Bovell, Dominique; Ellis, Darren; Mayer, Robert (Elsevier, 2026)
The Caribbean island-nation of Barbados represents an intriguing and valuable case study in air transport, with very little scholarly attention to date. This paper aims to investigate the state of air transport in the country over a decade-long period using three full years as reference points starting in 2014, then 2019 before onset of the COVID-19 global pandemic; and finally, 2023. The overall air market is assessed, then major markets by region are detailed; and lastly, the CARICOM air market’s direct links to Barbados are covered. By employing data from these three 12-month time periods over a decade (2014, 2019 & 2023), a clearer sense of the key insights into the country’s air transport industry’s size, scope and prospects can be achieved, while the composition of the air transport industry can also be better ascertained. Added to this, the likely future trajectory of the industry can be more accurately gauged and forecast. The core lessons and major implications from this study, not just for Caribbean nations and territories, but for other similarly sized and situated islands in places like the South Pacific and Indian Ocean, are many and varied. Chiefly, air transport development plays a pivotal role in not only connecting these communities with their neighboring regions and wider world, but in ensuring that island economies can diversify beyond a traditional focus on agriculture and tourism and expand into a wider array of sectors. In this context, the internal/national socio-economic benefits of air transport represent more than just the external links that air transport creates; but rather, national economic development and diversification with air transport acting as a key enabler.
Keywords: 3508 Tourism; 35 Commerce, Management, Tourism and Services; 3509 Transportation, logistics and supply chains; Barbados; air passenger traffic; national development; economic diversification